(untitled) (Research, Society and Development, 2020)
Aim: to analyze the quality of life of people with HIV in outpatient follow-up at a University Hospital in Rio de Janeiro. Method: a descriptive study with a qualitative approach. The sample consisted of 101 people with HIV in the care of a specialized care service at a university hospital. For data collection, a questionnaire of socioeconomic and clinical data and the WHOQOL-HIV bref instrument were used. Descriptive and inferential statistical analysis was used. Results: Most are women, aged between 18 and 38 years old, income of up to two minimum wages and complete high school. Quality of life was best assessed in the domains: psychological, social relationships and spirituality, religion and personal beliefs. Some socioeconomic variables showed statistically significant differences between the domains. Conclusion: the perception of QoL of people living with HIV was classified as intermediate in all domains. This fact reflects that, despite the existence of policies for access to Antiretroviral Therapy and health care available in the public network, social aspects must be considered for the populations in which HIV has been spreading.